1999
DOI: 10.1038/sj.leu.2401406
|View full text |Cite
|
Sign up to set email alerts
|

Early allogeneic transplantation for refractory or relapsed acute leukaemia following remission induction with FLAG

Abstract: The prognosis for patients with secondary AML, primary resistant AML or ALL and early (Ͻ12 months) relapse of acute leukaemia remains extremely poor with conventional chemotherapy. As part of a strategy to improve the outcome for these patients we have treated 22 consecutive patients (18 AML, four ALL, median age 35 years) with either primary resistant disease (n = 3), early relapsed leukaemia (n = 12) or secondary AML (n = 7, four RAEBt, two antecedant ALL and one antecedant Hodgkin's disease) with 'FLAG' ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…75 Allogeneic HSCT may provide the highest likelihood of cure, presumably related to the generation of an immunologically mediated graft-versus leukemia reaction not present with salvage chemotherapy, preferably after induction of a second CR. [76][77][78][79] However, there is a lack of prospective data to definitively demonstrate a superior outcome with such a strategy. If a suitable histocompatible sibling donor is not available, transplantation from an alternative donor such as a matched unrelated donor 80 or a haploidentical stem-cell donor 81,82 can be considered.…”
Section: Treatment Of Patients With Relapsed or Refractory Amlmentioning
confidence: 99%
“…75 Allogeneic HSCT may provide the highest likelihood of cure, presumably related to the generation of an immunologically mediated graft-versus leukemia reaction not present with salvage chemotherapy, preferably after induction of a second CR. [76][77][78][79] However, there is a lack of prospective data to definitively demonstrate a superior outcome with such a strategy. If a suitable histocompatible sibling donor is not available, transplantation from an alternative donor such as a matched unrelated donor 80 or a haploidentical stem-cell donor 81,82 can be considered.…”
Section: Treatment Of Patients With Relapsed or Refractory Amlmentioning
confidence: 99%
“…We have previously observed a high CR rate in response to FLAG in pgp-positive AML cases with primary resistance to DAT. 37 Furthermore, when using a flow cytometric assay of cell survival, we observed that in vitro responses to FLAG differed from DAT, depending upon pgp status. Pgp-positive AML blasts were more sensitive to the combination of fludarabine/AraC than to daunorubicin/AraC.…”
Section: P-glycoprotein (Pgp) In Amlmentioning
confidence: 89%
“…Thus, up to 50% of patients (10/12 with HR-AML and 7/12 with HR-ALL) were able to proceed to SCT. In contrast, only five out of 14 patients in CR proceeded to SCT in the GEMIA study 16 and 10/61 patients were able to receive consolidation with SCT after Months from Ara-amsa salvage with a combination of idarubicin and intermediatedose Ara-C. 22 The ability to treat a larger proportion of patients with SCT with the use of FLAG as a salvage regimen has been recently demonstrated, 23 although results from larger studies are awaited.…”
Section: Discussionmentioning
confidence: 99%